Insulin Analogues in the Treatment of Diabetes Mellitus - Pattanaphesaj, Juntana (Journal of Health Science of Thailand, 2017)
Diabetes mellitus, a chronic metabolic disorder, requires patients to take care themselves continuously including food control, exercise and active role in their treatment. All patients with type 1 diabetes mellitus, which their pancreas cannot produce enough insulin, need insulin to stay alive. They require multiple daily injections of insulin to mimic normal insulin secretion that varies with food consumed. Modifying the amino acid sequence of insulin molecule has developed newer analogues which the pharmacokinetic (i.e. absorption rate, time to peak) was changed. However, there is uncertainty about whether the use of insulin analogues is justified for all or some diabetic group because they are more expensive than conventional insulin. This article concludes from a systematic review and a meta-analysis which were undertaken to evaluate the clinical and economic implications of using insulin analogues for the treatment of diabetes mellitus, relative to conventional insulin. This information can help healthcare professionals in drug selection and drug use appropriately.